Solidarity perfected: beneficent christology in the Epistle to the Hebrews - McCruden, Kevin B. (Zeitschrift für die neutestamentliche Wissenschaft / Beihefte, 2008)
This book provides an exegetical and theological treatment of the theme of the perfection of Jesus in the Letter to the Hebrews by demonstrating how perfection terminology functions to comment on the beneficent, compassionate character of Jesus. To depict Jesus as being made perfect or complete is Hebrews' way of affirming Jesus' solidarity with, and compassion for, those socially persecuted Christians who constituted Hebrews' target audience.